McKenna Picabia : mai - juin 1992. - Van Tieghem, Jean-Pierre; González, Angel; Galerie des BEAUX ARTS Galerij, Brussel (Brussel : Galerie des Beaux-Arts Galerij, 1992)
Mckenna, Stephen ; Picabia, Francis
McKenna Picabia, Galerie des BEAUX ARTS Galerij, Brussel, mei - juni 1992
kunstcatalogus